Melodic Intonation Therapy: Back to Basics for Future Research - Zumbansen, Anna; Peretz, Isabelle; Hébert, Sylvie (Frontiers in Neurology, 2014)
We present a critical review of the literature on Melodic intonation therapy (MIT), one of the most formalized treatments used by speech-language therapist in Broca’s aphasia. We suggest basic clarifications to enhance the scientific support of this promising treatment. First, MIT is a program, not a single speech facilitation technique. The goal of MIT is to restore propositional speech. The rational is that patients can learn a new way to speak through singing by using language-capable regions of the right cerebral hemisphere. We argue that many treatment programs covered in systematic reviews on MIT’s efficacy do not match MIT’s therapeutic goal and rationale. Second, we distinguish between the immediate effect of MIT’s main speech facilitation technique (i.e., intoned-speech) and the effect of the entire program on language recovery. Many results in the MIT literature can be explained by this duration factor. Finally, we propose that MIT can be viewed as a treatment of apraxia of speech more than aphasia. This issue should be explored in future experimental studies.